Iridium(Ⅲ) complex-based phosphorescent probe for rapid, specific, and sensitive detection of phosgene. (June 2020) - Ma, Bin; Wang, Xuefeng; Gao, Shi; Qi, Lihong; Xu, Yong; Yang, Jinxing; Zuo, Guomin
Abstract: Due to the high toxicity and commercial availability of phosgene, there is an urgent need for rapid and reliable detection of phosgene in order to deal with a potentially severe threat to public security caused by terrorist and accidental industrial release. In this work, an iridium(Ⅲ) complex, Ir-OXIME, has been developed as a fast, highly sensitive and selective sensor for phosgene. Ir-OXIME displayed very weak phosphorescence due to quenching caused by the CN–OH moiety. After reacting with phosgene, the oxime is converted to a nitrile to form the brightly phosphorescent product, Ir–CN . Ir-OXIME exhibited a rapid response (<5 s), a low detection limit (2.4 nM), and a high selectivity towards phosgene in solution. The Stokes shift of Ir-OXIME reaches 294 nm, which prevented signal crosstalk and consequently improved sensing accuracy. Finally, test papers with Ir-OXIME immobilized on filter paper were designed and prepared as a practical detection tool of phosgene gas. Graphical abstract: A functional Ir(Ⅲ) complex, Ir-OXIME, was developed as a chemosensor for phosphorescence detection of phosgene with high sensitivity, specificity, and rapid optical response. Image 1 Highlights: A novel phosphorescent probe for phosgene was developed. The probe Ir-OXIME exhibited fast response to phosgene in less than 5 s. The unique probe Ir-OXIME exhibited giant Stokes shift (294 nm). The probe Ir-OXIME showed excellent sensitivity and high selectivity toward phosgene. The Ir-OXIME immobilized test paper can serve as a portable tool for phosgene sensing in the gas phase.